2022
DOI: 10.1007/s00787-022-02010-w
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal impact of psychosocial status on children’s mental health in the context of COVID-19 pandemic restrictions

Abstract: Emerging research suggests that the prevalence of child and adolescent mental health problems has increased considerably during the COVID-19 crisis. However, there have been few longitudinal studies on children’s mental health issues according to their social determinants in this context, especially in Europe. Our aim was to investigate the association between family socioeconomic status (SES) and children' mental health during the period of school closure due to COVID-19. Longitudinal data came from 4575 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Those problems were then associated with some routine changes or SDQ subscales changes, which finally led to parental stress. This result is similar to a longitudinal study about the psychosocial status and mental health of children in Europe [45]. An online survey in parents in the U.S. showed that the majority of them reported at least one symptom of parental burnout at the beginning of COVID-19.…”
Section: Discussionsupporting
confidence: 86%
“…Those problems were then associated with some routine changes or SDQ subscales changes, which finally led to parental stress. This result is similar to a longitudinal study about the psychosocial status and mental health of children in Europe [45]. An online survey in parents in the U.S. showed that the majority of them reported at least one symptom of parental burnout at the beginning of COVID-19.…”
Section: Discussionsupporting
confidence: 86%
“…The consequences of covid-19 are unfairly distributed in the population [ 49 ], and in this study, perceiving the family financial situation as poor and neither good nor bad were associated with negative psychosocial consequences of the covid-19 pandemic. That the effects of the pandemic particularly affected socioeconomically burdened groups has been shown earlier in children [ 50 ]. Studying a theoretical high school program was also associated with higher levels of covid-19 related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Studies often evaluate SES as a composite score [3,4,9,10], although the single components of SES may affect the outcome through different pathways, and the discovered effects may differ [20,49,50]. Further research is needed that investigates socioeconomic in uencing factors on the different dimensions of students' HRQoL during the pandemic separately, as this may provide further insight into the exact mechanisms at play.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that household socioeconomic status (SES), either as a composite score or as single components thereof, affected children's and adolescents' HRQoL during the COVID-19 pandemic [2][3][4][5][9][10][11][12]. While research prior to the pandemic has identi ed SES or components of it as an essential determinant of HRQoL [13][14][15][16][17], there is a lack of research examining causal factors for low HRQoL during the COVID-19 pandemic [4].…”
Section: Introductionmentioning
confidence: 99%